2012
DOI: 10.1155/2012/687291
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Epithelial Cells, Fibroblasts, and Osteoblasts in Dental Implant Titanium Topographies

Abstract: The major challenge for dental implants is achieving optimal esthetic appearance and a concept to fulfill this criterion is evaluated. The key to an esthetically pleasing appearance lies in the properly manage the soft tissue profile around dental implants. A novel implant restoration technique on the surface was proposed as a way to augment both soft- and hard-tissue profiles at potential implant sites. Different levels of roughness can be attained by sandblasting and acid etching, and a tetracalcium phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…[30][31][32] However, a microrough surface is recommended, which may be the best for HGFs. 33,34 In our study, we produced the original SLM specimen with a 7.57 µm in Ra value. Except for the layer-by-layer SLM manufacturing process, the roughness is also influenced by the partially melted particles.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] However, a microrough surface is recommended, which may be the best for HGFs. 33,34 In our study, we produced the original SLM specimen with a 7.57 µm in Ra value. Except for the layer-by-layer SLM manufacturing process, the roughness is also influenced by the partially melted particles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the surfaces of these nanostructures can effectively reduce inflammatory responses compared with surfaces of conventional implants [39][40][41]. Therefore, the proposed TNA structure possesses adaptive features that can successfully improve cell interaction with the implant materials and may potentially enhance osseointegration [42][43][44].…”
Section: mentioning
confidence: 99%
“…Peptide grafting may simultaneously increase the hydrophilicity of material surfaces. When cell suspensions with a fixed number of cells were placed on the surface of various groups, the hydrophilicity of the material surface determined the cell density in the specimens and the distribution area and affected the concentration of cell-secreted signal factors, thereby affecting subsequent cell behaviors [24][25][26][27].…”
Section: Surface Wettabilitymentioning
confidence: 99%
“…The osteoconductive properties of calcium phosphates can direct the growth of bone cells into the pores, and the release of calcium and phosphorus ions results in enhanced cell mineralization. Researchers have indicated that the detachment of calcium phosphate ceramic-coated implants is occasionally caused by insufficient binding between the calcium phosphate salts and the implant rather than poor integration of the calcium phosphate salts and the bone [17,[24][25][26][27][28]. When force is applied to an implant, pressure is applied to the ductile Ti and brittle calcium phosphate coating, causing a break in the coating and detachment from the implant.…”
Section: Cell Morphology On Varied Surfacesmentioning
confidence: 99%